Analysis of influencing factors of herpes zoster-related neuropathic pain on the head and face - Huiya SUN; Jun WANG; Tao YUAN; Ting FAN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To explore the influencing factors of herpes zoster neuralgia in order to provide reference for the diagnosis and the treatment of this disease. Methods We retrospectively analyzed 89 cases of craniofacial herpes zoster and 168 cases of non-craniofacial herpes zoster hospitalized in the First Affiliated Hospital of Wannan Medical College from January, 2019 to December, 2019. The demographic and clinical characteristics were compared between these two groups. Pearson analysis was used to determine the correlation between NLR and pain score and severity score of the skin lesions. Logistic regression was used to analyze the risk factors for herpes zoster neuralgia. Results There were no significant differences in age, gender, pain score and severity of skin lesions between the two groups when admitted to hospital. Patients with craniofacial herpes zoster had a higher rate of pustules, blood blister and necrosis than that with non-craniofacial herpes zoster (25.84% vs. 15.48%, χ2=4.05, P=0.044). Moreover, the NLR were higher in patients with craniofacial herpes zoster than that with non-craniofacial herpes zoster (4.11±1.62 vs. 2.35±1.51, t=6.27, P<0.05) at admission to hospital. NLR and severity of skin lesions were independent influencing factors for the severity of pain in acute phase of craniofacial herpes zoster (OR=1.758, 95%CI: 1.215~2.543 for NLR; OR=1.418, 95% CI: 1.034~1.944 for severity of skin lesions). The severity of skin lesions was an independent influencing factor for postherpetic neuralgia of craniofacial herpes zoster (OR=1.846, 95% CI: 1.167~2.922). Conclusions Patients with craniofacial herpes zoster have more severe inflammation. NLR and the severity of skin lesions are correlated with acute herpetic neuralgia. The severity of skin lesions is correlated with postherpetic neuralgia.